Curbing the Burn: Indonesia’s Collective Action Against Forest and Peatland Fires, 2015 – 2019 - Setiono, Dede Puji (KDI School of Public Policy and Management, Global Delivery Initiative, 2020)
Indonesia, a tropical country home to some of the world’s largest rainforests and peatlands, has long had a major forest fire problem. Fires occurred every year, and in 2015 forest and peatland fires scorched 2.6 million hectares of the archipelago, producing a toxic haze that blanketed the neighboring countries of Singapore and Malaysia. Thousands fell ill, and Indonesia suffered US$16 billion in economic losses. The disaster put the perpetrators of the fires—the forestry industry, palm oil industry, paper and pulp companies, and agricultural communities—in the spotlight. These actors used illegal fires to clear forests and peatland for commercial purposes, and did so with impunity. Forestry law enforcement was weak and the state agencies for fire prevention and suppression were not well coordinated. Communities residing in the vicinity of forests had low awareness of forest sustainability, making the situation worse. Although the government tried various policies to curb the recurrent fire problem, efforts proved futile. After the 2015 fires—the worst in a decade—the government took a new approach. Indonesia’s president, Joko Widodo, called on all actors affected by forest fires to work collectively. This government-led collective action included several state agencies, private companies, and communities at the village level, and distributed certain roles and responsibilities among the various parties. The government focused on strengthening law enforcement, suppressing forest fires, and restoring degraded peatland. Meanwhile, the private sector worked toward sustainable forestry industry practices, and local communities played a significant role in preventing and monitoring fire occurrences. Following the introduction of the new approach, there was a 93.6 percent reduction in hotspots (an indication of fire incidents) from 2015 to 2019. In addition, 700,000 hectares of peatland was restored and Indonesia reported a 60 percent drop on average in primary forest loss from January 2016 to June 2019.
Keywords: Reducing forest fires; Inter and intra-governmental relations; Roles and responsibilities; Corruption and patronage; Organizational capacity; Stakeholder engagement